Professionalism of Islamic Religious Education Teachers in Fostering the Morals of Students - Siti Solikah; Siti Rhoudlotul Jannah; Gunawan Gunawan (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2020)
The teacher as a professional educator has the main task, namely teaching, guiding, directing, training, evaluating, and evaluating students. Professional teachers are: Teachers who are able to carry out the duties and responsibilities as well as possible, able to carry out its role as a teacher in carrying out the main tasks and functions, which are able to plan learning, able to carry out the learning process, and assess and evaluate learning outcomes. This study aims to reveal the professionalism of Islamic Religious Education teachers in fostering the morals of students at SMK Al-Ma'arif Way Kanan. This study used a qualitative approach with case study design. Data collection is done by interview, observation and documentation. The results of this study indicate that: (1) PAI teacher professionalism is sufficient in carrying out its duties, in making learning plans, implementing learning and evaluating learning outcomes, but PAI teachers still need to improve their professionalism with various efforts. (2) Efforts in fostering the morals of students include a) integrated curriculum of intrakulikuler and extracurricular activities, b) exemplary, c) habituation, d) counseling guidance (3) supporting and inhibiting factors in fostering the morals of students, a) supporting factors of principals and teachers. b) The inhibiting factors are 1) Internal factors where the factors that exist in students themselves are the lack of awareness about moral education.2) External factors, a) the school environment, where the imperfect fence is there, the school environment, b) the family environment, where family environment that does not familiarize moral values ​​and religious atmosphere, c) the community environment, where the environment has bad habits and relationships.